LAKU SEMBAH CATUR SEBAGAI STRATEGI MENCAPAI KEMANUNGGALAN DENGAN TUHAN DALAM TJARIJOS REDI LAWOE - Trisnani Jati Winahyu; Turita Indah Setyani (Universitas Batanghari, 2026)
Tjarijos Redi Lawoe’s fairy tale tells of a character named Kasanredja that take a hike to Mount Lawu. The hiking trip is a spiritual laku that implemented as an effort to achieve the realization of Manunggaling Kawula Gusti 'unity with God'. The main problem of this research is how the representation of laku through sembah catur 'four worships’ in the Tjarijos Redi Lawoe. This research aims to prove that laku sembah catur is one of the strategies that can be carried out by anyone who wants to try to achieve unity with God or 'Manunggaling Kawula Gusti'. This research uses qualitative methods and an objective approach with the perspective of Javanese Religion. The results reveal that the laku sembah catur is divided into four stages: pendakian or hiking (sembah raga), tapa or meditation (sembah cipta), pencerahan or revelation (sembah jiwa), and manunggal or unity (sembah rasa). Based on the results of the research, it can be concluded that unity with God in the Tjarijos Redi Lawoe can be achieved by practicing laku sembah catur, so it can be stated that the practice is still relevant until nowaday.